2005
DOI: 10.1213/01.ane.0000184181.92140.7c
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Ambu?? Laryngeal Mask in Nonparalyzed, Anesthetized Patients

Abstract: We designed this multicenter trial to evaluate the performance and safety of the Ambu laryngeal mask, a new disposable supraglottic airway device, in patients scheduled for elective surgery. One-hundred-eighteen nonparalyzed, anesthetized patients (ASA physical status I-II, age, 18-65 yr, body mass index, 18-30 kg/m(-2)) receiving total IV anesthesia were included in this study. After device insertion, fiberoptic position and oropharyngeal leak pressure were determined at an intracuff pressure of 60 cm H2O. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
(9 reference statements)
7
24
1
3
Order By: Relevance
“…The i-gel TM was found to be the easiest of several SADs to insert in one manikin-based study 17 . Time taken to insert the AuraOnce TM was shorter in our study than in previous studies 5,6,10 and comparable to the results of another 12 which may be explained by a greater experience of all our operators with insertion of the AuraOnce TM device. Three patients required endotracheal intubation.…”
Section: Comparison With Other Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…The i-gel TM was found to be the easiest of several SADs to insert in one manikin-based study 17 . Time taken to insert the AuraOnce TM was shorter in our study than in previous studies 5,6,10 and comparable to the results of another 12 which may be explained by a greater experience of all our operators with insertion of the AuraOnce TM device. Three patients required endotracheal intubation.…”
Section: Comparison With Other Studiessupporting
confidence: 87%
“…Total success rate for AuraOnce TM insertion was 94.2% which corresponds with the results of other studies where overall success rate found was between 94% and 100% (ref. [4][5][6][10][11][12] ). First time success rates for the i-gel TM found in our study was 85.6% which is lower than the results published in recent cohorts.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer claims that this allows improved conformation to the shape of the airway. A multicentre study involving 118 patients demonstrated that the Ambu Laryngeal Mask is easy and quick to insert, providing a safe and efficient seal during positive pressure ventilation in non-paralysed patients undergoing elective surgery [9]. However, the study was limited by being non-comparative in design.…”
mentioning
confidence: 99%
“…The classical laryngeal mask airway (LMA), is a supraglottic airway device which simplified airway management [4]. The intubating laryngeal mask airway (The LMA-Fastrach™) was designed to facilitate intubationwhich can be done either blindly or via fibreoptic assistance [5].…”
Section: Introductionmentioning
confidence: 99%